Liberatory Research: Bridging the Gap Between Community Organizing and Research. Issue 2 (May 2023) - Lewis, Blu; Arriaga, Felicia
The North Carolina Black Leadership Organizing Collective (NCBLOC) began in 2015 and is in a 10-year process to develop Black-led movement organizations in North Carolina. Blu Lewis was one of the visionary architects of this initiative and refers to many of the ways we use research inside of the organization to work towards our goals. Felicia Arriaga joined NCBLOC as the network coordinator for one of NC BLOC's projects called the NC Statewide Police Accountability Network in 2019, moved into supporting cross movement organizing within NC BLOC, and now is the Development Manager for NC BLOC. We dive into a discussion about research and organizing strategies, how we can redefine validation, how we can pair research with narratives that represent our communities, how our values can align with our research, and how we can combat white supremacy culture that shows up in our research practices.